UTILIZATION OF INFORMATION SYSTEMS AT JUANDA HEALTH CENTER (Jurnal Abdimas Administrasi Kesehatan, 2022)
Despite the considerable attention which the growth of information systems technology in Juanda Health Center has received over the past two decades, research focusing on the development, confirmation, or extension of theories which explain the use of a wide range of technological innovations has had a mixed record of success. In particular, two issues stand out. SIMPUSKESMAS and frequently ambiguous definitions of utilization have led to relatively little replication of findings in various public settings. Second, relatively little empirical research has been under taken which explicitly incorporated and tested multiple alternative explanations of potential determinants of utilization, leading to continued fragmentation in the research literature. This analysis, using a national sample of state budgeting offices, draws on theoretical propositions offered over the past decade and more to operationalize utilization as the impact of technology on key organizational deciston-making processes and assess the relative explanatory power offered by three alternative explanations for the successful use of information systems technology. The findings suggest that unique combinations of three types of factors—environmental, managerial-organizational, and technological—will explain and account for the successful uutilization of technology in various settings.
Keywords: SIMPUSKESMAS